2022
DOI: 10.1155/2022/4134138
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram to Better Predict the In-Hospital Mortality of Trauma Patients with Sepsis in the Intensive Care Unit

Abstract: Background. Trauma has a high incidence and mortality worldwide, and sepsis is one of the main causes of mortality in trauma patients. Therefore, it is essential to identify the risk factors of in-hospital mortality for trauma patients with sepsis. Methods. Data were extracted from the Medical Information Mart for Intensive Care III database and divided into a training set and internal validation set, and another Chinese dataset was used as external validation set. Then, risk factors were estimated using univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…Sepsis is still the leading cause of death in patients elected to the ICU ( 15 , 18 ). In the present study, the 28-day mortality rate of septic patients with DM was 23.9% (n=533), which was higher than in general septic patients (10%-15%) ( 34 36 ). Regarding the hospitalization characteristics of the study population, we observed that survivors showed longer hospital and ICU stays than non-survivors, which was consistent with previous studies ( 24 , 37 ).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Sepsis is still the leading cause of death in patients elected to the ICU ( 15 , 18 ). In the present study, the 28-day mortality rate of septic patients with DM was 23.9% (n=533), which was higher than in general septic patients (10%-15%) ( 34 36 ). Regarding the hospitalization characteristics of the study population, we observed that survivors showed longer hospital and ICU stays than non-survivors, which was consistent with previous studies ( 24 , 37 ).…”
Section: Discussioncontrasting
confidence: 53%
“…There is a significant increase in the prevalence of DM in the elderly population ( 48 50 ), leading to exacerbation, poor prognosis, and increased mortality risk in sepsis ( 51 ). Additionally, serum biomarkers were important predictors in the surveillance of critically ill patients ( 34 , 36 , 52 55 ). Septic patients were often accompanied by hypoproteinemia due to capillary leakage, reperfusion injury, tissue ischemia, and inflammation ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 According to the World Health Organization (WHO) statistics, about 10% of deaths and 16% of disabled are caused by injury globally. 3 Injury is not only associated with an increased risk of adverse health outcomes (eg, venous thromboembolism, acute kidney injury, post-traumatic stress disorder, and sleep disorders) but also regularly poses a significant economic impact on patients' families and society. [4][5][6][7][8] It has been reported that the costs of injuryrelated care were estimated to exceed 400 billion dollars per year in the United States of America (USA) alone.…”
Section: Introductionmentioning
confidence: 99%